Analisis dan Perancangan Sistem Informasi Pendaftaran Jemaah haji & umroh berbasis website pada travel PT. Nur Mekahiyah Wisata - Aryanto; Muhammad Naufal Haykal (Computer Science and Information Technology, 2024)
This research is entitled "Analysis and Design of a Website-Based Information System for Registration of Hajj & Umrah Pilgrims at Travel PT. Nur Mekahiyah Wisata". The main objective of this research is to design and develop an effective information system to support the registration process, data management and consultation services for Hajj and Umrah pilgrims. The methods used include requirements analysis, system design, implementation and testing. The research results show that this system is able to improve operational efficiency, data accuracy and transparency of the registration process, as well as providing a more effective experience for users.